1983
DOI: 10.1073/pnas.80.8.2171
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for phosphorylation/dephosphorylation of rat liver acyl-CoA:cholesterol acyltransferase.

Abstract: Acyl-coenzyme A: cholesterol O-acyltransferase (ACATase; EC 2.3.1.26) is a membrane-bound microsomal enzyme that catalyzes the formation of long-chain fatty-acyl cholesterol esters in rat liver and other tissues. This enzyme is important in regulating the concentration of unesterified cholesterol in the cell. Having recently demonstrated that rat liver 3-hydroxy-3-methylglutaryl-coenzyme A reductase (HMG-CoA reductase; EC 1.1.1.34), the major regulatory enzyme in cholesterol biosynthesis, undergoes in vivo pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
1

Year Published

1983
1983
2001
2001

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(16 citation statements)
references
References 17 publications
1
14
1
Order By: Relevance
“…The regulation of enzyme activity could be achieved at several levels. For example, mammalian acylCoA:cholesterol acyltransferase activity is primarily controlled by protein phosphorylation (Gavey et al, 1983). A possible reason for the significant increase in oil content in the SLC7-7 transgenic Brassicaceae may be the result of differences in sn-2 acyltransferase regulation.…”
Section: ____mentioning
confidence: 99%
“…The regulation of enzyme activity could be achieved at several levels. For example, mammalian acylCoA:cholesterol acyltransferase activity is primarily controlled by protein phosphorylation (Gavey et al, 1983). A possible reason for the significant increase in oil content in the SLC7-7 transgenic Brassicaceae may be the result of differences in sn-2 acyltransferase regulation.…”
Section: ____mentioning
confidence: 99%
“…We recently reported the activations of rat aortic acid CEH (ACEH) and NCEH by both PKA and PKC to a similar extent in the presence of respective cofactors using selective inhibitors of two kinases (9). A cholesterol-esterifying enzyme, ACAT, is an integral membrane protein located in the endoplasmic reticulum, and evidence currently available for the involvement of phosphorylation in regulating ACAT is controversial; the dependence of ACAT activity on cholesterol availability has been documented in several studies (10,11): some evidence suggests the activation of ACAT by phosphorylation (12,13), whereas other evidence against the regulation of ACAT by phosphorylation has been presented (14,15).…”
mentioning
confidence: 97%
“…Studies with fibroblasts have shown that Ca2+-and phospholipid-dependent protein kinase C, which is activated by stimulation ofPtdIns turnover, controls the activity ofcertain enzymes involved in cellular LDL cholesterol (LDL-Chol) metabolism (3)(4)(5). This suggests an interrelationship between the PtdIns response and LDL-Chol metabolism, but it is not known whether low concentrations of LDL stimulate the PtdIns cycle in cells other than platelets.…”
mentioning
confidence: 99%